Manajemen Sekolah Ramah Anak dalam Meningkatkan Kesejahteraan Siswa di TK Islam Al Amin Kecamatan Tuntang - Zulfiana, Zulfiana; Kusumaningsih, Widya; Ginting, Rosalina BR (PGRI Kota Semarang, 2024)
Student welfare applies not only to students at the upper levels/adults but also to early childhood education. Similarly, as a school specializing in Early Childhood Education (ECE), Al Amin Islamic Kindergarten in Tuntang District has one way to achieve the goal of improving student welfare, namely through child-friendly school management. The school environment should create a sense of safety and comfort for students to learn and engage in other educational activities. This study aims to identify and describe child-friendly school management in enhancing student welfare at Al Amin Islamic Kindergarten in Tuntang District. This research is qualitative, with the research subjects being the school principal, teachers, students, parents, committee members, and students at Al Amin Islamic Kindergarten in Tuntang District. Data collection techniques include observation, interviews, and documentation. Data analysis employs the Miles and Huberman model with steps including data collection, data condensation, data presentation, and conclusion drawing. Data validity is ensured through increased diligence and the use of source and technique triangulation. The research findings indicate that child-friendly school management at Al Amin Islamic Kindergarten in Tuntang District operates very effectively. Supporting factors in the implementation of child-friendly school management at Al Amin Islamic Kindergarten in Tuntang District include cooperation and involvement of relevant stakeholders, while limiting factors include limited school land and insufficient BOSP funds. The impact of child-friendly school management at Al Amin Islamic Kindergarten in Tuntang District is the enhancement of student welfare and an improvement in school achievements in both academic and non-academic realms. Keywords: management, child-friendly school, student welfare